THREE LITTLE TRUTHS - Shortall, Eithne (New York : G.P. Putnam's Sons, 2020)
"The Husband's Secret meets Big Little Lies in this story of three women looking for a fresh start, and the love affairs, rivalries, and scandals found on the other side of the white picket fence."-- Provided by publisher.
Keywords: Women's Fiction; Married people -- fiction; Female friendship -- Fiction